A Dynamic Model of Raw Water Availability for Clean Water Demand in the Bedadung Watershed - Setyaningtyas, Rusdiana; Bisri, Mohammad; Suyono, Hadi; Santoso, Imam (Civil and Environmental Science Journal (CIVENSE), 2024)
The Bedadung watershed has undergone multiple changes in land cover, resulting in high erosion, sedimentation, flooding, and population pressure, which has caused an imbalance between the demand for clean water and the availability of raw water. Changes in land function resulted in decreasing infiltration capacity and increasing surface flow. This research aims to create a dynamic model of raw water availability in the Bedadung watershed to supply the domestic and non-domestic sectors in Jember. The availability of raw water is influenced by dynamic inputs such as population, industrial, and tourism growth, as well as the expansion of agricultural land. This model will produce a causal-loop diagram (CLD) between variables and then create a stock-flow diagram (SFD) using secondary data programmed by the Vensim PLE 10.1.1 application within 50 years. The modeling results show that the need for clean water increases over time, while the availability of raw water will decrease over time after 2025. In 2057, the clean water demand (463.29x106 m3y-1) was higher than the availability of groundwater (461.775x106 m3y-1), but it was still smaller than the availability of surface water (56,853,200x109 m3y-1). Water-carrying capacity will increase until 2025, then decrease over time.